2007
DOI: 10.1353/ol.2008.0011
|View full text |Cite
|
Sign up to set email alerts
|

Typology and the Linguistic Macrohistory of Island Melanesia

Abstract: Recent years have seen much discussion on the use and meaning of typological argumentation when reconstructing language history and language relations. We address the conclusions and methodology of a paper "Structural phylogenetics and the reconstruction of ancient language history" (Science, Sept. 23, 2005), which claims that, on the basis of a typological comparison, the non-Austronesian languages and (Austronesian) Oceanic spoken to the imediate east of new Guinea can be shown to belong to two unrelated gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Beyond these general points, this paper also constitutes a concrete response to some of the misapprehensions about Dunn et al (2005) found in Donohue and Musgrave (2007) (henceforth D&M). The most important claim made by D&M is that the apparent phylogenetic pattern might be a product of areal factors, in particular, contact with Oceanic languages.…”
mentioning
confidence: 93%
“…Beyond these general points, this paper also constitutes a concrete response to some of the misapprehensions about Dunn et al (2005) found in Donohue and Musgrave (2007) (henceforth D&M). The most important claim made by D&M is that the apparent phylogenetic pattern might be a product of areal factors, in particular, contact with Oceanic languages.…”
mentioning
confidence: 93%
“…As mentioned above both related and unrelated languages are sensitive to geographical distance in the amount of similarity they exhibit, so the claim that evidence had been found for a phylogenetic relationship was completely unfounded. In fact, in a more recent paper, written in response to a critique by Donohue and Musgrave (2007), the authors now admit that they are ‘unable to tease ancient contact and phylogeny apart’ (Dunn et al. 2007: 401).…”
Section: Some Resultsmentioning
confidence: 99%
“…Donohue and Musgrave (2007) take issue with the results: while they agree that structural features can and should be used in investigating linguistic history, they also contend that such features may be particularly prone to borrowing, especially in linguistic areas. This "would mean that conclusions such as those drawn by Dunn et al are particularly prone to controversy; without establishing that a particular set of correspondences in grammatical features are not due to areal influence, there can be no argument about the correspondence indicating a genetic relationship" (Donohue and Musgrave 2007: 350).…”
Section: 3mentioning
confidence: 91%